Fundamentals of cognitive psychology - Hunt, R. Reed (McGraw-Hill Higher Education, 2004)
This is a brief, affordable core text for courses in cognitive psychology. Thoroughly updated, the seventh edition offers coverage of perception, attention, memory, knowledge, problem solving, and emotion, in a friendly and accessible style. By discussing selected experiments rather than exhaustively surveying the empirical literature, the authors encourage students to appreciate the intricacies of problem-solving activity in cognition. The text incorporates real world examples, case studies, and key experiments on significant topics.